2005
DOI: 10.1111/j.1366-9516.2005.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Introduced invertebrates are important prey for a generalist predator

Abstract: Concern over biological invasions has drawn increased attention to the impacts of introduced predators or competitors, but not to the importance of introduced prey. North American forests are rich in introduced invertebrates, including species that represent relatively novel taxonomic or trophic guilds and show biased distributions among forest types. We analysed the diets of red‐backed salamanders, Plethodon cinereus, from three upland and three lowland forests to determine whether introduced prey are importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 29 publications
2
78
0
Order By: Relevance
“…Hatase et al (2006) found that stable isotope differences among Green Sea Turtles (Chelonia mydas) were consistent with individual differences in feeding habits. At the population level, plethodontid salamanders consume a wide range of prey that fluctuate at fine spatial scales among habitats, seasons, and with climatic events such as rain (Maerz et al 2005). Maerz et al (2006) showed that P. cinereus exhibit fine scale trophic polymorphisms related to differences in head morphology and diet within and among local habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Hatase et al (2006) found that stable isotope differences among Green Sea Turtles (Chelonia mydas) were consistent with individual differences in feeding habits. At the population level, plethodontid salamanders consume a wide range of prey that fluctuate at fine spatial scales among habitats, seasons, and with climatic events such as rain (Maerz et al 2005). Maerz et al (2006) showed that P. cinereus exhibit fine scale trophic polymorphisms related to differences in head morphology and diet within and among local habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Earthworms may also indirectly affect salamanders: some species of earthworms ingest recently fallen leaf litter and many species break down partially decayed organic matter (Edwards and Bohlen 1996), thereby potentially competing with the aboveground microinvertebrate community (reviewed in Brown 1995;Migge-Kleian et al 2006), the main food source for terrestrial salamanders (reviewed in Petranka 1998). There is also a direct trophic link between salamanders and earthworms, with salamanders consuming size-appropriate earthworms as a portion of their diet in some areas (Maerz et al 2005). Therefore, as in any typical three species 'community module' (sensu Holt 1997), earthworms and salamanders (with microinvertebrates) can interact directly and indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass (volume of prey item) was estimated by measuring maximum width (widest lateral points) and length {widest anterior to posterior points) for some prey items using a dissection microscope. Volume (mm^) was estimated as a cylinder using length as the axis and width as the diameter (Maerz et al 2005). Whenever possible, volume was estimated for up to five individuals from each family, and a mean volume was used to calculate biomass.…”
Section: Methodsmentioning
confidence: 99%